2019
DOI: 10.1111/jphp.13140
|View full text |Cite
|
Sign up to set email alerts
|

Lancemaside A from Codonopsis lanceolata prevents hypertension by inhibiting NADPH oxidase 2-mediated MAPK signalling and improving NO bioavailability in rats

Abstract: Shin and Han contributed equally to this work. AbstractObjectives This study investigated whether lancemaside A (LMA) can prevent hypertension and assessed the mechanisms of action of LMA in rats. Methods Hypertension was induced by chronic immobilization stress and nicotine administration. Hypertensive vehicle rats were treated with LMA (1, 20, or 40 mg/kg) or nifedipine (10 mg/kg) as a positive control daily for 3 weeks. Key findings In hypertensive vehicle rats, LMA dose-dependently reduced systolic blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…Previous studies have shown that CL and LMA have antioxidant [14] and anti-inflammatory effects [11] and even antihypertensive effects [15,16]. In addition, the findings that CL and LMA reduce peripheral resistance [15] or improve vascular endothelial function [17]…”
Section: Codonopsis Lanceolata Contributes To Ca 2+ Homeostasis By Mementioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have shown that CL and LMA have antioxidant [14] and anti-inflammatory effects [11] and even antihypertensive effects [15,16]. In addition, the findings that CL and LMA reduce peripheral resistance [15] or improve vascular endothelial function [17]…”
Section: Codonopsis Lanceolata Contributes To Ca 2+ Homeostasis By Mementioning
confidence: 96%
“…In addition, in prehypertensive adults, CL has been shown to reduce blood pressure by improving serum nitrite and catalase activity and reducing high-sensitivity C-reactive protein and malondialdehyde [16]. LMA has also been reported to exert an antihypertensive effect by increasing the bioavailability of nitric oxide through the inhibition of nicotinamide adenine dinucleotide phosphate oxidase 2 [17]. Additionally, LMA enhances nitric oxide synthesis in human umbilical vein endothelial cells [18].…”
Section: Codonopsis Lanceolata Contributes To Ca 2+ Homeostasis By Mementioning
confidence: 99%
“…In addition to CPPs, which are the main constituents and the most abundantly studied active ingredients in the last 5 years, Lobetyolin, lancemaside A, Saponins, Luteolin, Alkaloids and other constituents have also been studied by researchers. Among the diseases related to the action of these active ingredients ( Table 2 ), Lobetyolin ( He et al, 2020 ; Cheng et al, 2023 ), Luteolin ( Yu et al, 2023 ; Liu et al, 2024 ), polyacetylenes ( Wang M.-C. et al, 2022 ), Isorhamnetin ( Luan et al, 2019 ) and molecule compound D6 ( Tang X. et al, 2021 ) mainly act in the treatment of cancer, saponins act in digestive diseases ( Liu X. F. et al, 2021 ; Li et al, 2023 ), lancemaside A ( Lee et al, 2019 ; Shin et al, 2019 ) and atractylodesin III( Cao M. et al, 2019 ) act in cardiovascular diseases. In addition, in a mouse model of non-alcoholic fatty liver disease (NAFLD), Alkaloids attenuate lipid deposition in NAFLD by improving energy metabolism, reducing oxidative stress and endoplasmic reticulum stress, and thus act as hepatoprotective agents ( Fan C. et al, 2023 ).…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“…Kidney and testes were prepared for histopathatologic evaluation by fixing in a 10% solution of formalin and subsequently embedding the tissues in paraffin wax. Thereafter, the paraffin wax embedded tissues were sectioned, stained with Haematoxylin and Eosin, and examined microscopically (Shin et al, 2019).…”
Section: Histopathological Examinationmentioning
confidence: 99%